Pengaruh Fasilitas Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Di Suko Kopi Padang - Zahra Afra Arista; Nidia Wulansari (Lembaga Pengembangan Kinerja Dosen, 2023)
This research is motivated by the phenomenon of customer satisfaction which is thought to be due to facility factors and service quality. The purpose of this study was to determine and describe the effect of facilities and service quality at Suko Kopi Padang. This research is descriptive quantitative with sampling techniques using purposive sampling and a sample size of 371 respondents based on the Slovin formula. This research data collection technique uses a questionnaire with a Likert scale that has been tested for validation and reliability. Based on the results of the research analysis, it is concluded that the results of the t-test, for the facility variable (X1) produce a significant level of 0.000 <0.05, which means that there is an influence of the facility variable on customer satisfaction. And for the results of the t-test for the service quality variable (X2) results in a significance level of 0.000 <0.05, meaning that there is an influence of the service quality variable on customer satisfaction. Based on the results of the f-test, the significance level is 0.000 <0.05, indicating that simultaneously the facility variable (X1) and the service quality variable (X2) have an effect on customer satisfaction. Facility variables (X1) and service quality (X2) have an influence of 56.9%, while the rest is influenced by other variables.